All Days 1998
DOI: 10.2118/50594-ms
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Liquid Flow Through a Porous Medium by Ultrasonic Radiation

Abstract: A new method to enhance the oil production rate is irradiation of the near-wellbore region by an ultrasonic source. The limited success for the application of ultrasound in well stimulation to date, however, is due to the lack of understanding of the physical mechanisms between an acoustic wave field and a porous medium. In this paper the mechanism in which ultrasonic radiation deforms the walls of the pores in the shape of travelling transversal waves, is studied. A quantitative description of the mechanism i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…(mole fraction) 0.0172 iC 4 (mole fraction) 0.0070 nC 4 (mole fraction) 0.0265 iC 5 (mole fraction) 0.0179 nC 5 (mole fraction) 0.0179 C 6 (mole fraction) 0.0927 C 7 (mole fraction) 0.0752 C 8 (mole fraction) 0.0919 C 9 (mole fraction) 0.0740 C 10 (mole fraction) 0.0557 C 11 (mole fraction) 0.0466…”
Section: Experiments Proceduresmentioning
confidence: 99%
See 2 more Smart Citations
“…(mole fraction) 0.0172 iC 4 (mole fraction) 0.0070 nC 4 (mole fraction) 0.0265 iC 5 (mole fraction) 0.0179 nC 5 (mole fraction) 0.0179 C 6 (mole fraction) 0.0927 C 7 (mole fraction) 0.0752 C 8 (mole fraction) 0.0919 C 9 (mole fraction) 0.0740 C 10 (mole fraction) 0.0557 C 11 (mole fraction) 0.0466…”
Section: Experiments Proceduresmentioning
confidence: 99%
“…[7][8][9] Over the past decades, the ultrasound method as an economical and environmentally friendly technology has attracted much interest for prevention and treatment of small deposits in the wellbore, production facilities, and near wellbore region. [10][11][12][13][14] Recently, ultrasonic waves have been introduced as a useful method for enhancing oil/heavy-oil production, crude oil upgrading, and prevention or removal of asphaltene deposits from the wellbore and near wellbore region. [13,[15][16][17][18][19][20][21] In the following part, the most relevant studies on application of ultrasonic waves in oil industry are presented.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For instance, the ultrasonic wave is able to effectively reduce the viscosity of heavy oil through aquathermolysis reaction, but such effect becomes pale in the light oil stored in low-permeability reservoirs due to the low viscosity in its nature [28] , [29] . Recently, the ultrasonic wave has also been proved to change the relative permeability of oil in low-permeability reservoirs [30] , [31] , [16] , [32] , [33] , [34] , [35] . In addition, with high energies, the ultrasonic waves may also change the microstructure of cores [36] .…”
Section: Introductionmentioning
confidence: 99%
“…Reddi and Challa 5) and Reddi and Wu 6) reported that ultrasonic waves can increase not only the mobility of liquid ganglia but the porosity of the soil as well, resulting in a decrease in viscosity and buoyant pressure. Aarts et al 7) studied the mechanism of induced net flow by ultrasound. Poesio et al 8,9) found that ultrasound has a significant effect on the pressure gradient and temperature of core samples at constant liquid flow rate.…”
mentioning
confidence: 99%